Potassium sodium niobate (KNN) lead-free piezoceramics: a review of phase boundary engineering based on KNN materials - Mohd Ali Piah, Hidayah; Abd Rashid, Mohd Warikh; Azlan, Umar Al-Amani; Mohd Hatta, Maziati Akmal (AIMS Press, 2023)
Lead zirconia titanate (PZT) is the most often used piezoelectric material in various electronic applications like energy harvesters, ultrasonic capacitors and motors. It is true that PZT has a lot of significant drawbacks due to its 60% lead content, despite its outstanding ferroelectric, dielectric and piezoelectric properties which influenced by PZT's morphotropic phase boundary. The recently found potassium sodium niobate (KNN) is one of the most promising candidates for a new lead-free piezoelectric material. For the purpose of providing a resource and shedding light on the future, this paper provides a summary of the historical development of different phase boundaries in KNN materials and provides some guidance on how to achieve piezoelectric activity on par with PZT through a thorough examination and critical analysis of relevant articles by providing insight and perspective of KNN, which consists of detailed evaluation of the design, construction of phase boundaries and engineering for applications